2018
DOI: 10.31487/j.dobcr.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Is it all just an Akt - you’d be SMAD to believe it! Role of TGFβ1 in oral cancer metastasis

Abstract: Introduction: TGFβ1 activates both SMAD and non-SMAD dependent signalling pathways but their role in oral cancer cell migration and metastasis is little known. The aim of this research was to investigate the role of TGFβ1-induced signalling pathways in oral cancer cell migration and to establish whether the inhibition of the associated pathway may be a suitable target for chemotherapeutic drug design to control oral cancer cell metastasis. Materials and Methods: SDS-PAGE and Western blot techniques were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…TGFβ has been shown to activate Akt, leading to cell migration in prostate cancer [ 44 ]. TGFβ1 stimulates the phosphorylation of SMAD (Sma and Mad proteins), MAPK, and Akt in head and neck cancer but stimulated the migration of cancer cells in an Akt-dependent manner [ 45 ]. In prostate cancer, CXCR4 is overexpressed, and a loss of the tumour suppressor PTEN was reported to activate Akt and regulate the CXCL12/CXCR4 signalling pathway in metastasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ has been shown to activate Akt, leading to cell migration in prostate cancer [ 44 ]. TGFβ1 stimulates the phosphorylation of SMAD (Sma and Mad proteins), MAPK, and Akt in head and neck cancer but stimulated the migration of cancer cells in an Akt-dependent manner [ 45 ]. In prostate cancer, CXCR4 is overexpressed, and a loss of the tumour suppressor PTEN was reported to activate Akt and regulate the CXCL12/CXCR4 signalling pathway in metastasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ has been shown to activate Akt, leading to cell migration in prostate cancer [27]. TGFβ1 stimulates the phosphorylation of SMAD, MAPK and Akt in oral cancer, but stimulated the migration of oral cancer cells in an Akt-dependent manner [28]. In prostate cancer, CXCR4 is overexpressed and loss of the tumour suppressor PTEN was reported to activate Akt and regulate the CXCL12/CXCR4 signalling pathway in metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Akt has been reported to be abundant in the nucleus in many cancer cells yet, the mechanism of translocation, biological importance and activity has not yet been established [165]. Published data from our group also revealed that EGF (Epidermal Growth Factor), TGFα (Transforming Growth Factor α), TGFβ1(Transforming Growth Factor β1) and NGF (Nerve Growth Factor) can stimulate head and neck cancer cell migration and a specific PI3k/Akt pathway inhibitor such as PI103 or MK2206 can effectively block growth factor-induced cell migration [166,167]. Study from our research group also suggested that receptor tyrosine kinase inhibitors such as Gefitinib and Erlotinib inhibited the migration of head and neck cancer cells by inhibiting both Akt and MAPK phosphorylation [168].…”
Section: Akt In Hnscc Metastasismentioning
confidence: 99%